Seed and Root Endophytic Fungi in a Range Expanding and a Related Plant Species - Geisen, Stefan; Kostenko, Olga; Cnossen, Mark C.; ten Hooven, Freddy C.; Vreš, Branko; van der Putten, Wim H. (Frontiers in Microbiology, 2017)
Climate change is accelerating the spread of plants and their associated species to new ranges. The differences in range shift capacity of the various types of species may disrupt long-term co-evolved relationships especially those belowground, however, this may be less so for seed-borne endophytic microbes. We collected seeds and soil of the range-expanding Centaurea stoebe and the congeneric C. jacea from three populations growing in Slovenia (native range of both Centaurea species) and the Netherlands (expanded range of C. stoebe, native range of C. jacea). We isolated and identified endophytic fungi directly from seeds, as well as from roots of the plants grown in Slovenian, Dutch or sterilized soil to compare fungal endophyte composition. Furthermore, we investigated whether C. stoebe hosts a reduced community composition of endophytes in the expanded range due to release from plant-species specific fungi while endophyte communities in C. jacea in both ranges are similar. We cultivated 46 unique and phylogenetically diverse endophytes. A majority of the seed endophytes resembled potential pathogens, while most root endophytes were not likely to be pathogenic. Only one endophyte was found in both roots and seeds, but was isolated from different plant species. Unexpectedly, seed endophyte diversity of southern C. stoebe populations was lower than of populations from the north, while the seed endophyte community composition of northern C. stoebe populations was significantly different southern C. stoebe as well as northern and southern C. jacea populations. Root endophyte diversity was considerably lower in C. stoebe than in C. jacea independent of plant and soil origin, but this difference disappeared when plants were grown in sterile soils. We conclude that the community composition of fungal endophytes not only differs between related plant species but also between populations of plants that expand their range compared to their native habitat. Our results suggest that fungal endophytes of two Centaurea species are not able to systemically infect plants. We highlight that endophytes remain poorly studied and further work should investigate the functional importance of endophytes.